1999
DOI: 10.1097/00000539-199901000-00035
|View full text |Cite
|
Sign up to set email alerts
|

The "Second Gas Effect" Is Not a Valid Concept

Abstract: We studied the effects of N2O on the ratio of alveolar (end-tidal) concentration to inspired concentration of the second gas (enflurane) and on its blood concentration in humans. Nitrous oxide did not affect the alveolar or blood concentration of the second gas under controlled constant volume ventilation. The "second gas effect" is not a valid concept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Some perceived benefits may be overstated. For example, nitrous oxide is purported to speed induction of anaesthesia via the second gas effect but this has not been consistently borne out by clinical studies [13].…”
Section: Discussionmentioning
confidence: 99%
“…Some perceived benefits may be overstated. For example, nitrous oxide is purported to speed induction of anaesthesia via the second gas effect but this has not been consistently borne out by clinical studies [13].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Sun et al 9 reported that the second gas effect was not a valid concept. Although there are some experimental design differences between our study and theirs, our results do not support their suggestion.…”
Section: Resultsmentioning
confidence: 99%
“…The second gas effect was proposed by Epstein et al (1) and was proven in the consecutive study (13). However, in the study carried out by Sun et al (14), it was determined that the F A /F i ratio and arterial blood concentration did not show any difference with the addition of N 2 O to enflurane in the first five minutes; they claimed that the second gas effect is not a clinically valid concept. When Mutoh et al (15) compared the dog groups in which N 2 O was added and was not added to sevoflurane and isoflurane, they determined that N 2 O had not improved the quality of mask induction and that the concentration and second gas effects had been minimal.…”
Section: Discussionmentioning
confidence: 97%
“…In the study of Sun et al (14) in which they did not accept the second gas effect, the ventilation parameters were not kept constant, and the cardiac effects of N 2 O were ignored. The effects of N 2 O on the functions of the cardiovascular system are increasing the HR and arterial blood pressure mildly, and thus the cardiac output, by stimulating the sympathetic nervous system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation